Peranan sub sektor perikanan terhadap produk domestik regional bruto dan kesempatan kerja di kota samarinda (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2016)
The purpose of this research is studying what the fisheries subsector role was as moderating variable for Gross Regional Domestic Product and employment Opportunities in Samarinda or not. This study uses a series of data over the years 2000-2014 and analysis tools using multiple linear regression method and moderating variable with software SPSS 21.0. On the based this research showed that the gross regional domestic product gave a positive significant influence on employment opportunities in Samarinda. Fisheries subsector gave a negative significant influence on employment opportunities but fisheries subsector was not as a moderating variable because it can not indicate as a strongthness or a weekness gross regional domestic product against employment opportunities in Samarinda.Keyword: Fisheries Subsector, Gross Regional Domestic Product, Employment Opportunities and Moderating Variable.